NUMERASI SISWA SMA IPA DAN IPS SERTA IMPLIKASINYA TERHADAP PENIADAAN JURUSAN DI KURIKULUM PROTOTYPE - Jackson Pasini Mairing; Dita Monita; Dony Apriatama; Wiyogo (JURNAL PENDIDIKAN, 2022)
The prototype curriculum has the characteristics of eliminating majors and emphasizing literacy. This study aims to describe the differences in mathematical literacy (numbering) between students majoring in science and social science. Numeration is a student's ability to solve problems in the context of everyday life. Will the elimination of this department has an impact on the successful implementation of the prototype curriculum? This study uses a quantitative approach. The type of research is experimental with post-test two groups design. The population is high school students from one of the public schools in North Barito Regency, Central Kalimantan. The sample was selected using purposive sampling because face-to-face learning is limited to a shifting system. The instruments are two numerical problems. The results showed that the mathematical literacy of science students was more than social science students. However, overall student literacy is still low. These conditions need to be anticipated in the prototype curriculum by creating learning that encourages social interaction, positive dependence, and emphasizes the use of mathematical problems.